Factors associated with incomplete tuberculosis preventive treatment: a retrospective analysis of six-years programmatic data in Cambodia - Yom An; Kim Eam Khun (Scientific Reports, 2024)
Abstract Tuberculosis (TB) preventive treatment (TPT) effectively prevents the progression from TB infection to TB disease. This study explores factors associated with TPT non-completion in Cambodia using 6-years programmatic data (2018–2023) retrieved from the TB Management Information System (TB-MIS). Out of 14,262 individuals with latent TB infection (LTBI) initiated with TPT, 299 (2.1%) did not complete the treatment. Individuals aged between 15–24 and 25–34 years old were more likely to not complete the treatment compared to those aged < 5 years old, with aOR = 1.7, p = 0.034 and aOR = 2.1, p = 0.003, respectively. Individuals initiated with 3-month daily Rifampicin and Isoniazid (3RH) or with 6-month daily Isoniazid (6H) were more likely to not complete the treatment compared to those initiated with 3-month weekly Isoniazid and Rifapentine (3HP), with aOR = 2.6, p < 0.001 and aOR = 7, p < 0.001, respectively. Those who began TPT at referral hospitals were nearly twice as likely to not complete the treatment compared to those who started the treatment at health centers (aOR = 1.95, p = 0.003). To improve TPT completion, strengthen the treatment follow-up among those aged between 15 and 34 years old and initiated TPT at referral hospitals should be prioritized. The national TB program should consider 3HP the first choice of treatment.